Health consequences of Obstructive Sleep Apnoea Syndrome - Szewczyk, Kamila; Szewczyk, Bartłomiej; Krzesłowska, Wiktoria Julia; Pytel, Paulina; Wiśniewski, Szymon; Hołownia, Weronika (Journal of Education, Health and Sport, 2024)
Introduction: Obstructive Sleep Apnoea Syndrome (OSAS) is a common sleep disorder characterized by recurrent episodes of partial or complete upper airway obstruction during sleep. OSAS affects millions of people worldwide, with varying degrees of severity. It contributes to a range of adverse health outcomes, including cardiovascular, neurocognitive, metabolic, and psychosocial effects. Understanding the wide-ranging impact of OSAS is crucial in emphasizing the importance of early recognition, accurate diagnosis, and tailored interventions to improve the quality of life for affected individuals. Aim of the study: The aim of this study is to explore the diverse health consequences of OSAS and highlight the importance of early recognition, accurate diagnosis, and tailored interventions for managing this sleep disorder effectively. By understanding the impact of OSAS on various aspects of health, we can emphasize the need for comprehensive evaluation and a multidisciplinary approach to improve the overall health of individuals affected by OSAS.